Study of the energy flow and Global Warming Potential (GWP) of alfalfa and maize silage production with different water supply sources (a case study: Qazvin Plain) - Ehsan Khodarezaie; Korous Khoshbakht; Hadi Veisi; Mohammad Reza Nazari (علوم محیطی, 2023)
Introduction: Energy use in agriculture has grown faster than other sectors of the global economy. In developing countries, most agricultural systems consume significant amounts of energy to increase production and food security. Energy consumption leads to the emission of greenhouse gases and environmental pollutions in the agriculture sector. Besides, the use of fossil fuels in the production process and transfer of inputs emits greenhouse gases, which in turn cause global warming and climate change. Analyzing and good understanding of energy flow and Greenhouse Gas (GHG) emissions in agricultural production systems can help to optimize crop management practices thereby reducing environmental problems.Qazvin Plain is one of the most important agricultural plains in Iran, which along with the use of groundwater, has the largest irrigation canal network in the country. Differences in agricultural water supply sources can lead to differences in energy consumption and GHG emissions as electricity and other inputs may be affected. Alfalfa and maize silage are major forage crops in Qazvin Plain. Alfalfa and maize silage need a relatively high irrigation water requirement. This paper evaluates the energy flow and Global Warming Potential (GWP) of alfalfa and maize silage farms with two different water supply sources (well and canal) in Qazvin Plain.Material and methods: The data were collected through face-to-face interviews with farmers in the years 2018-2019. Energy indices were estimated based on the analysis of farm inputs and outputs. GWP was calculated using the Life Cycle Assessment (LCA) method and SimaPro 8.2 software. GHGs were calculated using the conversion coefficients presented by the IPCC GWP 100 method. Results and discussion: The output energy values of maize silage and alfalfa were calculated as 232726, 191812 MJ ha-1 for well water irrigation system and 234167 and 248060 MJ ha-1 for the canal water irrigation, respectively. Results showed higher net energy values for alfalfa (176218 MJ ha-1) and maize silage (169192 MJ ha-1) in canal water irrigation system compared to well water irrigation (63115 MJ ha-1 and 132956 MJ ha-1 for alfalfa and maize silage, respectively) mainly because of the relatively lower input energy. The results showed that the highest and lowest values of input energy were related to alfalfa production with well water irrigation (128697 MJ ha-1) and maize silage with canal water irrigation (64975 MJ ha-1), respectively. Also, the energy use efficiency of maize silage (3.6) and alfalfa (3.4) were higher in canal water irrigation systems compared to well water irrigation systems (2.3 for maize silage and 1.49 for alfalfa). In the well water irrigation systems, GWP was calculated to be 7466.9 kg CO2-eq ha−1 and 7995.7 kg CO2-eq ha−1 for maize silage and alfalfa, respectively. These values were 5533.3 kg CO2-eq ha−1 and 4947.6 kg CO2-eq ha−1 for maize silage and alfalfa in the canal water irrigation systems, respectively. Electricity and direct emission showed the highest share of total energy consumption and GHG emission.Conclusion: Generally, our results showed that energy consumption and GWP were lower in the canal irrigation systems than well irrigation systems mainly as a result of electricity used for water pumping in well irrigation operations. It can be inferred from the present study that for efficient use of resources and decreasing environmental problems in the study area, practices such as optimal management of irrigation water, conservation tillage, and optimal management of chemical fertilizers can help to achieve these goals.